DNA METHYLTRANSFERASE 1 (DNMT1) GENE ACTIVITY IN HUMAN LYMPHOMAS CORRELATES WITH ABERRANT p53 GENE EXPRESSION - Qayum, Iftikhar; Ashraf, Muhammad (Journal of Ayub Medical College Abbottabad, 2006)
Background: The DNA Methyltransferase 1 (DNMT1) gene has been implicated as a mutagen for tumor suppressor genes by causing hypermethylation and subsequent TA mutations of CpG islands located in the promoter regions of these genes. The present study was undertaken to determine if increased DNMT1 gene activity correlated with increased aberrant p53 gene expression in human lymphomas. Methods: The study was undertaken on randomly selected archival human lymph nodes comprising 50 normal or reactive lymph nodes and 50 lymphoma lymph nodes. These were subjected to Fluorescent In Situ Hybridization (FISH) using oligonucleotide Antisense probes for the DNMT1 and the p53 mRNA according to standard FISH protocols. Percent cells stained, mean '˜dots' stained per cell and staining signal intensity were taken as the criteria for comparing control and lymphoma lymph nodes. Quantitation of probe signals was done both by manual visualization of fluorescent signals and computer based image analysis. Correlation analysis was performed by calculation of Pearson's correlation coefficient. Results: Data indicated significantly increased expression of the DNMT1 and the p53 mRNA in lymphoma cases as compared to controls (p<0.001). Moreover significant correlation was obtained for the expressions of these two genes in lymphomas (p<0.001), but not in control lymph nodes. Conclusion: Increased DNMT1 gene activity may contribute to increased p53 gene expression in human lymphomas, supporting a mutagenic role for the DNMT1 gene. Key Words: Fluorescent In Situ Hybridization, p53, DNA Methyltransferases, lymphomas.